Punishing evil and promoting good: the moderating role of subject reputation in the effect of emotion on sharing debunking information. - CHAO, Fan; ZHOU, Qiao; YU, Guang; SUN, Yuan (Humanities & Social Sciences Communications, 2025)
Disseminating debunking information is an effective strategy for addressing rumours on social media. This study investigates the role of emotions—specifically emotional valence and discrete emotions—in the sharing of debunking information, with a focus on the moderating effect of the reputation of the rumour's subject. We tested the research model proposed in this study using data sourced from Sina Weibo. The results revealed that emotional valence, whether positive or negative, significantly enhances the likelihood of sharing debunking information. Additionally, anticipation, trust, anger, sadness, and disgust all exhibit significant positive effects on sharing. Notably, the influence of emotional valence is contingent on the reputation of the rumour's subject; both positive and negative sentiments prove more effective when the subject has a positive reputation, while the effect of negative sentiments is amplified when the subject is associated with a negative reputation. Additionally, post hoc analyses underscore the critical moderating role of subject reputation in shaping the impact of discrete emotions such as fear, sadness, and trust. This study not only deepens our theoretical understanding of how emotions influence the sharing of debunking information but also provides practical insights for stakeholders, helping them develop more effective debunking information disseminating strategies based on the reputation of the rumour's subject.